The potential and impact of blockchain technology on KYC process in the Philippines - Paradeza, Steven Maverick M.
The cost of complying to know-your-customer (KYC) is one of the major challenges of financial institutions. During the process, customer satisfaction is also affected generating negative experience since they need to do repeated tasks. This paper maps the current KYC process in the Philippines based on the Anti-Money Laundering Act (AMLA) and assesses blockchain technology as a solution to the said problems. With blockchain technology attributes, a solution design is proposed by automating the verification process, making the information available in the eyes of the regulator in case of disputes, reducing business costs, and reducing time of verification, therefore leading to better customer experience.